Boosting Zn-ion adsorption in cross-linked N/P co-incorporated porous carbon nanosheets for the zinc-ion hybrid capacitor. Issue 30 (26th July 2021) - Zhang, Hanfang; Chen, Zhensheng; Zhang, Yihe; Ma, Zequn; Zhang, Yingge; Bai, Liqi; Sun, Li
Abstract : Zn-Ion adsorption is boosted in cross-linked N/P co-incorporated porous carbon nanosheets derived from cellulose for enhanced capacity in a zinc-ion hybrid capacitor. Abstract : Zinc-ion hybrid capacitors (ZHC) are promising new types of energy storage devices that combine many advantages of supercapacitors and batteries. However, the bottlenecks of low energy density and inferior cyclic stability urgently need to be addressed, and constructing advanced cathode materials is a feasible and effective strategy to overcome this barrier. Herein, we report a ZHC with enhanced performance obtained by incorporating N and P heteroatoms into cross-linked porous carbon nanosheets (CNPK) for promoting the Zn-ion adsorption. The ex situ XPS results during the charging and discharging processes proved the existence of –OH and Zn 2+ chemical adsorption. Theoretical simulations revealed that the doping of N and P atoms can weaken the energy barrier of the reaction between the cathode and Zn 2+ ; graphitic nitrogen and graphitic phosphorus are particularly significant for the reduction of the reaction energy barrier. Consequently, CNPK exhibited a high capacitance of 233 F g −1 at 0.5 A g −1 and low equivalent series resistance. The assembled aqueous ZHC demonstrated a capacity of 103.2 mA h g −1 (232.2 F g −1 ) at 0.1 A g −1, energy density of 81.1 W h kg −1, power density of 13.366 kW kg −1, and an excellent cyclic stability of 101.8% capacitance retention after 10 000 cycles in ZnSO4 electrolyte. A quasi-solid-state ZHC was assembled to verify the practical application, which delivered a high capacity of 141.0 mA h g −1 at 0.1 A g −1 and a remarkable energy density of 89.3 W h kg −1 . This work opens the door to the study of porous carbon materials for high-performance ZHCs.